Characterisation of Malaysian residual soils for geotechnical and construction engineering - Marto, Aminaton; Kasim, Fauziah (Universiti Teknologi Malaysia, 2003)
Residual soils are formed from the weathering process of rocks. Although there are many research has been conducted on engineering properties of residual soils, the study on mineralogy, microstructure, microfabric and chemical composition of residual soils, despite of its importance, is still lacking. In addition, correlations developed between the engineering properties of granitic residual soils are also still lacking. The knowledge of behaviour and correlations amongst the soil properties is important and useful for design works and construction practices. Properties of mineralogy, microstructure and microfabric and chemical composition can be correlated to physical and engineering characteristics of residual soils. This information can be used in the design of structures placed on and in residual soils. The objectives of the study are to determine engineering properties, chemical composition, mineralogy, microstructure and microfabric of granitic residual soil, as well as to catalogue briefly on properties of residual soils, and to form related correlation charts of granitic residual soils of Peninsular Malaysia, to produce basic catalogue of the properties, and to generate correlations between the properties of the granitic residual soils. Samples of the granitic residual soils at various depths were taken from nineteen locations in Peninsular Malaysia, using thin-walled and Mazier samplers. Basic properties of soils, i.e., natural water content, grain size distribution, specific gravity, and Atterberg limits were determined. In addition, one-dimensional consolidation tests were performed using oedometer apparatus for the determination of the compressibility characteristics and the coefficient of permeability of the soils. The shear strength of the soils was determined by using Geotechnic Digital System (GDS), which includes three digital controllers, digital presure interface and Bishop Wesley’s triaxial cell for an isotropic consolidated undrained test with measurement of pore water pressure. The Scanning Electron Microscopy (SEM) and X-Ray Fluorescent (XRF) were used to analyse the mineralogy, microstructure and microfabric of granitic soils. The pH meter, Spectrophotometer DR4000 and Atomic Absorption Spectrophotometer (AAS) were used for the determination of the chemical compositions and parameter of the residual soils. The results show that, the granitic residuals soils can be categorised as silty and/or clayey sand of low to high plasticity. The natural moisture content increases with increasing depth and clay content and in the range of 10% to 46 %. Specific gravity values are found to be in the range between 2.50 and 2.70. The compression index, coefficient of consolidation, and coefficient of permeability are in the range of 0.11 – 0.42, 1.53 m2/year – 49.64 m2/year, and 1.1 x 10-11m/s – 9.86 x 10-9 m/s, respectively. The effective cohesion values are in the range of 0 – 36.4 kN/m2, while the effective friction angles are in the range of 16º – 31º. The study on the mineralogy and the microstructure show that quartz and kaolinite are two major minerals that present in the granitic residual soils while montmorillonite, illite and muscovite are the minor minerals. The presence of kaolinite minerals forms microfabric of flaky shape whereas quartz exists in granular form with clothed contacts. The study on microstructure of the residual soils show the existence of clay matrix with pH values of between 4.34 to 6.93, which indicate that the residual soils are acidic. The concentration of sulphate and chloride are in the range of 2.21 ppm to 17.58 ppm and 6 ppm to 75 ppm, respectively. The test results also show that the concentration of anion increases while the cation decreases with increasing distance from the surface of clay minerals. The values of cation exchange capacity (CEC) for the soil samples were found to be in the range 0.34 meq/100 g to 12.88 meq/100 g. Several correlations between the engineering properties of the residual soils were determined. Amongst them, the liquid limit, plasticity index and compression index were found to be increasing with increasing clay content. The compression index and coefficient of volume compressibility increase with increasing void ratio. The compression index and the initial void ratio increase, but the effective friction angle decreases, with increasing clay content. The correlation between CEC versus pH values, loss on ignition (LOI) versus aluminium oxides (Al2O3), sulphate and chloride contents with depths, were developed for the residual soils of the Eastern part of Peninsular Malaysia. The results show that CEC values are influenced by the high pH values. The sulphate and chloride, both found existed in the granitic soil samples, showed that they increased with depth. The correlation between Silicon Oxide and plasticity index is found to be inversely related; this is due to the existence of quartz minerals, which reduce the plasticity of soils, whereas Al2O3 and Fe2O3 in clay minerals increase the plasticity of the soils. The generated correlations can be used as guides for preliminary designs for geotechnical structures constructed on or in residual soil of Peninsular Malaysia.